Strategic alliance team diversity, coordination, and effectiveness - Zoogah, D.; Vora, D.; Richard, O.; Peng, Mike (Routledge, 2011)
Drawing upon literatures on strategic alliances, teams, and diversity, we propose that strategic alliance team diversity warrants further examination. We suggest that strategic alliance team coordination moderates the relationship between strategic alliance team diversity and effectiveness. Specifically, we hypothesize that coordination strengthens the negative relationship between observable diversity characteristics of nationality and gender and team effectiveness. We also argue that coordination strengthens the positive relationship between nonobservable diversity characteristic of functional background and team effectiveness. Results from 109 team members, 44 team leaders, and 34 alliance executives involved with 44 strategic alliance teams in 15 firms partially support our hypotheses.